2015
DOI: 10.1097/ta.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of early trauma-induced coagulopathy

Abstract: Traumatic-induced coagulopathy (TIC) is a hemostatic disorder that is associated with significant bleeding, transfusion requirements, morbidity and mortality. A disorder similar or analogous to TIC was reported around 70 years ago in patients with shock, hemorrhage, burns, cardiac arrest or undergoing major surgery, and the condition was referred to as a "severe bleeding tendency," "defibrination syndrome," "consumptive disorder," and later by surgeons treating US Vietnam combat casualties as a "diffuse oozing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 73 publications
2
115
1
Order By: Relevance
“…Therefore, the pathophysiologic mechanism of ATC has been emphasized as being different from that of DIC [13,27,41,54]. However, thrombin generation with marked decrease in fibrinogen and D-dimer elevation was observed [13,27,41,54], suggested to be consistent with the pathophysiology of DIC.…”
Section: Atc As Disseminated Intravascular Coagulation With a Fibrinomentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, the pathophysiologic mechanism of ATC has been emphasized as being different from that of DIC [13,27,41,54]. However, thrombin generation with marked decrease in fibrinogen and D-dimer elevation was observed [13,27,41,54], suggested to be consistent with the pathophysiology of DIC.…”
Section: Atc As Disseminated Intravascular Coagulation With a Fibrinomentioning
confidence: 97%
“…Almost all severely traumatized patients, especially those with ATC, are diagnosed as having DIC according to the scoring systems of the ISTH and Japanese Association for Acute Medicine [48,52,53]. However, no anatomopathologic evidence, e.g., intravascular formation of fibrin and thrombotic occlusion of vessels, has been demonstrated, and consumption coagulopathy leading to platelet and coagulation factor deficiency is not a common finding in patients with ATC [27].…”
Section: Atc As Disseminated Intravascular Coagulation With a Fibrinomentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Current studies have revealed that neurohormonal activation, systemic inflammation and widespread endothelial damage may similarly have an important influential role, and the etiology of traumarelated coagulopathy is multifactorial. [7,8] Much mystery still surrounds changes in coagulation taking place in the period after injury. This study developed a rabbit model of traumatic shock with abdominal injuries to characterize…”
Section: Introductionmentioning
confidence: 99%